Endogean and cavernicolous Coleoptera of the Balkans. XVII. A new species of the genus Speluncarius Reitter, 1886 (Coleoptera, Carabidae, Harpalinae, Pterostichini) from Croatia - Hlaváč, Peter; Lakota, Ján; Čeplík, Dávid (Zootaxa, 2016)
The genus Speluncarius Reitter, 1886 (Harpalinae, Pterostichini) is made up by anophthalmous or almost blind species. The genus is related to Tapinopterus Schaum, 1858, which contains numerous species from the Balkan-Anatolian region and have more or less developed eyes. Speluncarius is distributed in the Western Palaearctic region; 26 species and one subspecies are known from Italy, the Balkan Peninsula and Turkey. The genus is classified in five subgenera, Elasmopterus Kraatz, 1886 (6 spp.); Hypogearius Jeannel, 1953 (3 spp.); Hypogium Tschitscherine, 1900 (1 sp.); Pontotapinus Guéorguiev & Lohaj, 2008 (1 sp.) and Speluncarius (s.str.) Reitter, 1886 (15 spp.) (Sciaky, 1982; Bousquet, 2003; Guéorguiev & Lohaj, 2008; Casale et al., 2013).